1963
DOI: 10.1083/jcb.18.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis by Isolated Pea Nucleoli

Abstract: A new method is described for the preparation of active, nucleus-free nucleoli and chromatin in relatively high purity and in sufficient quantities to permit biochemical and electron microscopic investigation. This method consists of disintegrating previously isolated nuclei by grinding with glass beads in an isotonic medium thus liberating structurally intact nucleoli and chromatin threads. Nucleoli and chromatin are then purified by differential centrifugation in Ficoll solutions. A study of the chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, there is no evidence that this is related to the controversial idea of mRNA translation in the nucleus [25,26]. Yet, it should be noted that, during the 1960s, data were published reporting that amino acids could be incorporated into peptides within isolated nucleoli [27][28][29]. The high protein complexity of the nucleolus implies that either the biogenesis of ribosomes is a surprisingly complex process and/or that the nucleolus carries out additional functions, consistent with the theory of a plurifunctional nucleolus [30,31].…”
Section: Bioinformatic Analysesmentioning
confidence: 99%
“…However, there is no evidence that this is related to the controversial idea of mRNA translation in the nucleus [25,26]. Yet, it should be noted that, during the 1960s, data were published reporting that amino acids could be incorporated into peptides within isolated nucleoli [27][28][29]. The high protein complexity of the nucleolus implies that either the biogenesis of ribosomes is a surprisingly complex process and/or that the nucleolus carries out additional functions, consistent with the theory of a plurifunctional nucleolus [30,31].…”
Section: Bioinformatic Analysesmentioning
confidence: 99%
“…Pioneering studies localizing incorporation of very brief pulses of radiolabeled amino acids by electron and light microscopy identified the nucleoplasm and particularly, the nucleolus as fractionally minor but clear sites of protein synthesis [142][143][144][145]. A classic study from Wu and Warner [146] showed that most rapidly labeled nuclear proteins are synthesized in the cytoplasm.…”
Section: Nuclear Translation: Who Ordered That?mentioning
confidence: 99%
“…According to data recently compiled by Vincent et al, (51), for instance, nucleoli from a wide variety of sources consist mostly of proteins (85-90%), RNA representing only 5-10% of the mass of these organelles. The situation is a great deal more uncertain as regards the actual concentration of DNA within nucleoli, and relevant data, therefore, differ markedly with authors and sources of material (5,8,9,34,37,38,51). These widely divergent reports undoubtedly result in part from the difficulty of preparing nucleoli free of contaminating chromatin.…”
mentioning
confidence: 99%